A history of the Reformed Church, Dutch, The Reformed Church, German, and the Moravian Church in the United States - Corwin, Edward Tanjore (American church history series, 1895)
A history of the Reformed Church, Dutch / E. T. Corwin -- A history of the Unitas Fratrum, or Moravian Church, in the United States of America / J. T. Hamilton.